Saving Mir with a rope trick. - Oberg, J. (IEEE spectrum)
Using a fabled ?skyhook? of engineering folklore (known as firefly), Russia's ailing Mir space station may soon lift itself by its own bootstraps into a higher, more stable orbit. That feat, though, is raising fears at NASA that the development of its supposed replacement, the International Space Station (ISS) will be upset. At present, Mir is orbiting without a crew. The last two cosmonauts to visit the station returned to Earth in June 2000. The next crew is set to go up in November 2000, according to MirCorp, the private consortium that agreed to lease the station for commercial purposes. What's more, in an effort to add years to the station's lifespan, cosmonauts will begin testing a new propulsion technology some time later this year or next. The heart of the new technology is an electrodynamic tether, a long thin wire that will attach to Mir and draw electrons from Earth's ionosphere. As with an electric motor, this current-carrying wire will experience a force as it passes through Earth's magnetic field, a force that will, it is hoped, stabilize Mir's altitude